A class of multivalent non-Bazilevic functions involving the Cho-Kwon-Srivastava operator - Wang, Zhi-Gang; Tai-Wang, Heng; Sun, Yong (Tamsui Oxford Journal of Mathematical Sciences)
The main purpose of this paper is to derive some new properties for a class of p-valent non-Bazilevič functions involving the Cho-Kwon-Srivastava operator, such results as subordination and superordination properties, convolution properties, coefficient estimates, sufficient conditions for starlikeness and sufficient conditions for functions belonging to this class are obtained.